Remote electrophysiological cardiotocography (eCTG), evaluation of feasibility in complicated pregnancies from 32 until 37 weeks gestational age in a home@hospital setting (HASTA): A prospective cohort study protocol - Sofie van Weelden; Loes Monen; M. Beatrijs van der Hout-van der Jagt; Judith O. E. H. van Laar (PLoS ONE, 2026)
Introduction High-risk pregnancies, including those complicated by pre-eclampsia, fetal growth restriction or preterm pre-labor rupture of membranes, often require hospitalization for fetal and maternal monitoring. Home monitoring may reduce the psychological and family burden, improve patient satisfaction, and lower health care costs. The primary diagnostic tool for fetal home monitoring is cardiotocography (CTG). However, conventional CTG can suffer from poor signal quality due to maternal obesity or movements. Since electrophysiological cardiotocography (eCTG) relies on electrical activity in cardiac and uterine muscles, signal quality is less impacted by obesity and motion artefacts than with conventional CTG, making eCTG also interesting for home monitoring. As remote eCTG is self-administered, it eliminates the need for professional support at home, potentially increasing autonomy and satisfaction. Nevertheless, signal quality of self-administered eCTG in the preterm period is unknown. This prospective cohort study will assess the feasibility of self-administered eCTG, using NemoRemote in a hospital setting between 32–37 weeks of gestation, simulating home use. Methods In this single center prospective cohort study, 60 pregnant patients (≥18 years) with a singleton high-risk pregnancy from 32 until 37 weeks of gestational age will be recruited. Remote self-administered eCTG will be performed either daily for patients admitted to the hospital, or at least twice a week at the outpatient clinic. The primary outcome is the proportion of successful eCTG recordings. Secondary outcomes include maternal and perinatal outcomes, patient and healthcare professional satisfaction, and a cost analysis. Conclusion This study will provide valuable insights into the technical and logistical feasibility of self-administered eCTG monitoring in high-risk pregnancies, with potential implications for the implementation of remote fetal monitoring. A hospital-based feasibility study was chosen over an implementation study to safely assess signal quality of remote eCTG before broader application. Trial registration This trial is registered on the Dutch trial register “Onderzoeksportaal” (NO. NL-OMON57084) https://onderzoekmetmensen.nl/en/trial/57084 . Date registered: 05/11/2024 and the international trial register “ClinicalTrials.gov” (NO. NCT06859177); http://clinicaltrials.gov/study/NCT06859177 . Date registered: 05/03/2025